COVID-19 and Sex Differences: Mechanisms and Biomarkers (2020)
Men are consistently overrepresented in Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection, and COVID (COrona- VIrus-Disease)-19 severe outcomes, including higher fatality rates. These differences are likely due to gender-specific behaviors, genetic and hormonal factors, and sex differences in biological pathways related to SARS-CoV-2 infection. Several social, behavioral and comorbid factors are implicated in the generally worse outcomes in men as compared with women. Underlying biological sex differences and their effects on COVID-19 outcomes, however, have received less attention. The present review summarizes the available literature regarding proposed molecular and cellular markers of COVID-19 infection, their associations with health outcomes, and any reported modification by sex. Biological sex differences characterized by such biomarkers exist within healthy populations and also differ with age- and sex-specific conditions, such as pregnancy and menopause. In the context of COVID-19, descriptive biomarker levels are often reported by sex, but data pertaining to the effect of patient sex on the relationship between biomarkers and COVID-19 disease severity/outcomes are scarce. Such biomarkers may offer plausible explanations for the worse COVID-19 outcomes seen in men. There is the need for larger studies with sex-specific reporting and robust analyses to elucidate how sex modifies cellular and molecular pathways associated with SARS-CoV-2. This will improve interpretation of biomarkers and clinical management of COVID-19 patients by facilitating a personalized medical approach to risk stratification, prevention, and treatment.